Indigenous persons with disability in remote Australia: research methodology and Indigenous community control. Issue 7 (9th August 2018) - Gilroy, John; Dew, Angela; Lincoln, Michelle; Ryall, Lee; Jensen, Heather; Taylor, Kerry; Barton, Rebecca; McRae, Kim; Flood, Vicki
Abstract: Decolonisation aims to deconstruct the hegemonic traditional Western academic practices and values that oppress Indigenous peoples. Decolonising research methodologies is a relatively new practice in disability research in colonised nations. This paper details the Indigenous community-controlled research methodology that underpinned a disability research project with the An angu and Yarnangu of Central Australia, 'Walykumunu Nyinaratjaku: To Live a Good Life'. The project aimed to identify and explore how to support Indigenous people with a disability in the Ngaanyatjarra Pitjantjatjara Yankunytjatjara (NPY) Lands to live a good life. The research was structured on a decolonising methodology to situate the control and governance of the research with the Indigenous peoples. Our experience could assist other disability researchers working with Indigenous peoples in remote communities.